2019
DOI: 10.32737/2221-8688-2019-4-558-564
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Metals With Dihydrazones of Succinic Acid Dihydrazide

Abstract: Bis-(3,5-di-tert-butyl-salicylidene) dihydrazone of succinic acid dihydrazide was synthesized and its analogue-reduced azomethine bond. The complexes of Mn (II) and Fe (II) with these ligands were obtained. Based on the data of IR-, electron spectroscopy and elemental analysis, of the obtained complexes is assumed the binuclear structure. The possibility of catalytic reduction of the azomethine bond with NaBH 4 to the corresponding succinic acid bis-(2-hydroxybenzyl) succinic dihydrazide was shown. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…3). The shift of the bands in the complexes suggests that the metal ion is coordinated by two oxygen atoms and one nitrogen atom of the aminodiacetic fragment [16][17].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…3). The shift of the bands in the complexes suggests that the metal ion is coordinated by two oxygen atoms and one nitrogen atom of the aminodiacetic fragment [16][17].…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Previously, we have found that metal complexes of hydrazones of salicylic acid derivatives have signi cant inhibitory and urease activity [19]. At the same time, succinic and nicotinic acid hydrazones and their complexes have high bactericidal and fungicidal activity [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[14,15]. Previously, we found that metal complexes of hydrazones of salicylic acid derivatives have significant inhibitory and urease activity [16], succinic and nicotinic acid hydrazones and their complexes have high bactericidal and fungicidal activity [17,18].…”
mentioning
confidence: 99%